Validation of housekeeping genes for qPCR in maize during water deficit stress conditions at flowering time - Decima Oneto, Cecilia Andrea; Bossio, Adrian Ezequiel; Faccio, Paula Daniela; Beznec, Ailin; Blumwald, Eduardo; Lewi, Dalia Marcela (2017)
Plant stress studies are increasingly being based on gene expression. The analysis of gene expression requires sensitive, precise, and replicable measurements for specific mRNA sequences. Real-time RT-PCR is nowadays the most sensitive method for the detection of low abundance mRNA. A stable reference gene is mandatory to obtain reliable quantitative real-time PCR (qPCR) analysis results. Real-time RT-PCR is referred with one or several internal control genes, which should not fluctuate during treatments. In this study, we have chosen eight genes as candidates of possible reference genes for maize (Zea mays L) during water deficit stress at flowering time: a-tubulin, 3`phosphate glyceraldehyde dehydrogenase (GAPDH), 18S ribosomal subunit, protein 13S ribosomal, actin, zein, invertase, and starch synthase IIB. The eight reference genes candidates were tested on maize plants around flowering time, under three different conditions: before water deficit (BWD), under water deficit (WD) and after water deficit (AWD). Results from the three experimental conditions indicated that protein 13S ribosomal gene was the most stable among all the reference genes tested. This result suggests that protein 13S ribosomal gene can be used as internal control (housekeeping) for qPCR analysis in maize plants under water deficit stress during flowering time.